Cellular ultrastructural studies and biological effects of copper complexes of phenanthroline derivatives. (29th March 2019) - Nunes, Patrique; Marques, Fernanda; Pinheiro, Teresa; Pedro Matos, António; Correia, Isabel; Costa Pessoa, João
Abstract : Introduction: Phenanthroline (phen) is a bioactive molecule and a versatile building block for chelation of various metals yielding complexes with interesting biological and physiological properties [1 ]. In the area of medicinal chemistry and in the search for new compounds with antitumor activity, coordination complexes with metal ions have been studied by some of us [2–4 ]. Herein, three Cu(II)-complexes, [Cu(Phen)2 (H2 O)](NO3 )2 [1 ], [Cu(Me2 Phen)2 (H2 O)](NO3 )2 [2 ], and [Cu(amPhen)2 (H2 O)](NO3 )2 [3 ] were studied for their stability in cell medium, their cellular uptake and distribution and their biological effects. Materials and methods: The stability in cellular medium was evaluated by UV-Vis and EPR spectroscopies. The antitumor activity in A2780 (ovarian) and PC3 (prostate) cancer cells was evaluated by the MTT assay; the copper cellular uptake and distribution within cells were evaluated by ICP-MS and nuclear microprobe; the mechanism of action or intracellular targets were assessed by electron microscopy (TEM). Results : The cytotoxic activity of complexes [1–3 ] was dependent on the type of cells and differed only for shorter incubation times. Complex [2 ] was the most cytotoxic. The complexes interact with serum albumin, present in the incubation cell media, modifying their uptake and cytotoxicity in a way that depends on the type of cells and the species formed with serum albumin. The uptake profile, cellular distribution and mechanisms of action were elucidated by nuclear microprobe and TEM studies. These studies in the ovarian cells revealed that complexes provoked an elemental imbalance, in particular by the increase of intracellular Ca ions, nuclear and mitochondrial alterations, especially for complexes [1 ] and [2 ], the most active compounds that resulted in apoptotic blebs. Discussion and conclusions: Overall, these studies that combine spectroscopic, nuclear and electron microscopy techniques provide unique and complementary information on the biological effects of these Cu-complexes, and contribute to shed more light onto their mechanisms and cellular targets and on the role speciation in cell media plays in the biological activity, should we consider their potential use as anticancer agents.